Ultrasonography of the Vagus Nerve in the Diagnosis of Parkinson’s Disease - Ovidijus Laucius; Renata Balnytė; Kęstutis Petrikonis; Vaidas Matijošaitis; Neringa Jucevičiūtė; Tadas Vanagas; Vytautas Danielius (Parkinson's Disease)
Background. It is currently impossible to diagnose Parkinson’s disease (PD) in the premotor phase even though at the time of motor symptom onset the number of already degenerated dopaminergic substantia nigra neurons is considerable. Degeneration of the dorsal nucleus of the vagus nerve (VN) has been reported early in the disease course, and it could lead to impaired function of the VN, resulting in certain nonmotor symptoms of PD. Therefore, we raised a hypothesis that the loss of VN neurons could result in a smaller diameter of the VN among PD patients. Methods. 20 PD patients and 20 age- and gender-matched individuals without any neurodegenerative disease were enrolled in a pilot study. The diameters of the right and left VNs were measured using ultrasonography, their average was calculated, and the narrower VN diameter was noted separately. Results. No difference was found between the PD and control groups neither in the average VN diameter (mean 1.17; 95% confidence interval (CI) 1.10–1.24 vs. 1.13; 1.07–1.18, mm; p=0.353) nor in the narrower VN diameter (mean 1.11; 95% confidence interval (CI) 1.02–1.20 vs. 1.07; 1.02–1.13, mm; p=0.421). The narrower VN diameter and the average VN diameter were not able to distinguish between PD patients and controls (area under curve (AUC) = 0.588, 95% CI = 0.408–0.767, and p=0.344; and AUC = 0.578, 95% CI = 0.396–0.759, and p=0.402). Conclusions. To conclude, no differences were found in VN diameter between the PD and control groups. Therefore, our data do not support the hypothesis that PD could be associated with a smaller diameter of the VN.